(untitled) (Journal of Medical & Health Sciences Review, 2025)
Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia due to insulin resistance or deficiency, leading to multisystem complications. Optimizing patient care requires insight into prescribing patterns, comorbidities, treatment outcomes, adherence, and health literacy. This study evaluated the Drug Utilization Review (DUR) of antidiabetic medications, analyzing prescriptions by age, gender, and family history, assessing adherence and patient comprehension, and determining the economic burden of therapy. A descriptive observational study was conducted on 50 DM patients in the endocrinology ward of Lady Reading Hospital, Peshawar. Data on demographics, medical history, lab findings, and medication adherence were collected. Diabetic neuropathy (56%), cellulitis with foot ulcers (54%), and nephropathy (44%) were the most common complications. Combination therapy, particularly triple therapy, was preferred over monotherapy for better glycemic control. Medication adherence was suboptimal, with only 14% demonstrating excellent compliance, correlating with elevated HbA1c levels. Findings highlight the need for patient education, adherence strategies, and optimized pharmacotherapy to improve outcomes and reduce complications in tertiary healthcare settings.